What’s special about the ethical challenges of studying disorders with altered brain activity? - Cassaday, Helen J. (Springer-Verlag, 2014)
Where there is no viable alternative, studies of neuronal activity are conducted on animals. The use of animals, particularly for invasive studies of the brain, raises a number of ethical issues. Practical or normative ethics are enforced by legislation, in relation to the dominant welfare guidelines developed in the UK and elsewhere. Guidelines have typically been devised to cover all areas of biomedical research using animals in general, and thus lack any specific focus on neuroscience studies at the level of the ethics, although details of the specific welfare recommendations are different for invasive studies of the brain. Ethically there is no necessary distinction between neuroscience and other biomedical research in that the brain is a final common path for suffering, irrespective of whether this involves any direct experience of pain. One exception arises in the case of in vitro studies, which are normally considered as an acceptable replacement for in vivo studies. However, to the extent sentience is possible, maintaining central nervous system tissue outside the body naturally raises ethical questions. Perhaps the most intractable challenge to the ethical use of animals in order to model neuronal disorder is presented by the logical impasse in the argument that the animal is similar enough to justify the validity of the experimental model, but sufficiently different in sentience and capacity for suffering, for the necessary experimental procedures to be permissible.